The Role of Parietal Epithelial Cells in the Pathogenesis of Podocytopathy - Li, Zhi-hang; Guo, Xiao-yan; Quan, Xiao-ying; Yang, Chen; Liu, Ze-jian; Su, Hong-yong; An, Ning; Liu, Hua-feng (Frontiers in Physiology, 2022)
Podocytopathy is the most common feature of glomerular disorder characterized by podocyte injury- or dysfunction-induced excessive proteinuria, which ultimately develops into glomerulosclerosis and results in persistent loss of renal function. Due to the lack of self-renewal ability of podocytes, mild podocyte depletion triggers replacement and repair processes mostly driven by infiltrated stem cells or resident parietal epithelial cells (PECs). In contrast, when podocyte recovery fails, activated PECs contribute to the establishment of glomerular lesions. Increasing evidence suggests that PECs, more than just bystanders, have a crucial role in various podocytopathies, including minimal change disease, focal segmental glomerulosclerosis, membranous nephropathy, diabetic nephropathy, IgA nephropathy, and lupus podocytopathy. In this review, we attempt to dissect the diverse role of PECs in the pathogenesis of podocytopathy based on currently available information.